Functional Gait Can Be Affected by Noise: Effects of Age and Cognitive Function: A Pilot Study - Buyle, Margot; Azoidou, Viktoria; Pavlou, Marousa; Van Rompaey, Vincent; Bamiou, Doris-Eva (Frontiers in Neurology, 2021)
Background: The ageing process may degrade an individual’s balance control, hearing capacity and cognitive function. Older adults perform worse on simultaneously executed balance and secondary tasks (i.e., dual-task performance) than younger adults and may be more vulnerable to auditory distraction. Aim: The purpose of this study was to determine the effect of passive listening on functional gait in healthy older versus younger adults, and to investigate the effect of functional gait, hearing ability and cognitive functioning on dual-task performance. Methods: Twenty young and twenty older healthy adults were recruited. Functional gait (Functional Gait Assessment in silent and noisy condition), hearing function (audiogram; Speech in Babble test) and cognitive ability (Cambridge Neuropsychological Test Automated Battery) were measured. Results: Overall, a significant difference between functional gait performance in silent versus noisy conditions was found (p = .022), with no significant difference in dual-task cost between the two groups (p = .11). Correlations were found between increasing age, worse functional gait performance, poorer hearing capacity and lower performance on cognitive function tasks. Interestingly, worse performance on attention tasks appeared to be associated with a worse functional gait performance in the noisy condition. Conclusion: Passive listening to multi-talker babble noise can affect functional gait in both young and older adults. This effect could result from the cognitive load of the babble noise, due to the engagement of attention networks by the unattended speech.